Improving Partnership Relations between Suppliers of Metal Products and a Digital Marketplace Company on the Market of Contract Manufacturing: A Case Study - Monika GÓRSKA (Communications of International Proceedings, 2021)
The article discusses a digital marketplace company that digitizes the traditional contract manufacturing process of metal products with the help of a distributed network of production partners (distributed production). The form of the so-called digital marketplace forces the examined company to constantly improve the tools that enable the provision of its services to potential buyers and suppliers. The article presents the form of cooperation between companies and a digital marketplace company and premises for establishing and improving such relations. The article also presents how the activities implemented by the examined company affect the cooperation conditions both on the part of customers and production partners of the company. The paper presents the procedures, methods and tools used in the process of providing given services, as well as their in-depth analysis.
Keywords: Digital Marketplace; Improvement of Partnership Relations; Forms of Cooperation.